Experimental study on H-section steel beam-columns under cyclic biaxial bending considering the effect of local buckling. (1st November 2018) - Cheng, Xin; Chen, Yiyi; Niu, Li; Nethercot, David A.
Highlights: Experimental study on H-section beam-columns subjected to combined axial force and cyclic biaxial bending. Coupling effect of local buckling and plastic deformation is investigated. Strength, ductility and energy absorption capacity have been extracted. Torsional effects accompanying bi-directional bending are found to be ignorable. Abstract: Due to multidirectional ground motions generated by earthquakes, structural members will be subjected to biaxial bending effects, where the occurrence of yielding and/or buckling about one principal axis induces unfavourable deteriorations about the other principal axis. The experimental research on cyclic biaxial bending behavior of steel H-section members is conducted. A specially designed "3D-hinge-sliding" testing system composed of a universal rotatable hinge and three sliding devices is established to apply the axial force and cyclic biaxial moments to the specimens. Eleven steel H-section beam-columns with different width-thickness ratios for the flanges and webs, together with different axial force ratios and loading directions are employed. Measures of performance, including failure mechanism, interaction curves, ductility and energy absorption capacity, have been extracted from the measured data. The responses are found to be strongly influenced by the interactions between the local buckling and plastic deformation effects of the plate elements.